Investigation of biopharmaceutical and physicochemical drug properties suitable for orally disintegrating tablets - Asami Ono; Takumi Tomono; Takuo Ogihara; Katsuhide Terada; Kiyohiko Sugano (International Association of Physical Chemists (IAPC), 2016)
The purpose of this study was to evaluate the biopharmaceutical drug properties suitable for orally disintegrating tablets (ODTs). The net charge at pH 7.4, log D6.5, the highest dose strength, solubility in water, dose number, and elimination t1/2 of 57 ODT drugs and 113 drugs of immediate-release (IR) formulations were compared. These drugs were classified according to the Biopharmaceutical Classification System (BCS). A lower dose strength and a longer elimination t1/2 have been observed as characteristic properties of ODTs. The proportion of basic drugs was higher in the ODTs than in the IR. A significant difference was not observed between the ODT and the IR formulation for log D6.5, solubility in water, and dose number. The distributions of the ODT and IR formulations among each BCS class were similar, suggesting that an ODT can be developed regardless of the BCS class of a drug.